El rigor científico en la investigación cualitativa (2011)
ABSTRACT: For research methodology scholars, rigor issues related to the quality of the research is a core issue. The objective of this article is to show the status of rigor in qualitative research, its main criteria, the differences in its interpretation and application, ethics and the researchers’ social commitment. For such purpose, issues related to the instrument, field work, analysis and theoretical sampling, theoretical saturation and researcher’s integrity, are analyzed. Validity, reliability, objectivity versus subjectivity, credibility, confirmability and transferability concepts, as well as evaluation guidelines, are reviewed. Those are necessary elements to all the ones who are involved in research from different perspectives and interests.